A Rare Case of Canine Metastatic Spermatocytic Tumor without Sarcomatous and Anaplastic Variants - Lee Eun-Joo (Sciendo, 2021)
Spermatocytic tumor is a rare testicular tumor, which is originated from gonocytes. It is characterized by the histological feature of tripartite which is composed of large, medium, and lymphocyte-like small cells. It is well-known that spematocytic tumor is benign, thus a good prognosis is expected after simple resection. Metastatic spermatocytic tumor is extremely rare and usually accompanied by histological variants including sarcomatous changes and anaplastic variants. In this case, however, we report a canine metastatic spermatocytic tumor without prominent sarcomatous changes and anaplastic variants. The mass was composed of three kinds of cells including large, medium, and small cells with high pleomorphism. The neoplastic cells had an indistinct cytoplasmic border and mitotic figures were frequently observed. The primary spermatocytic tumor metastasized to the abdominal organs one month after the resection, and the dog died 13 months after the surgery. Thus, careful follow-up is recommended after surgical resection of canine spermatocytic tumor even though metastasis in spermatocytic tumors is rare.